Oximeter and BPM on Smartwatch Device Using Mit-App Android with Abnormality Alarm - Bedjo Utomo; Syaifudin, Syaifudin; Dian Setioningsih, Endang; Hamzah, Torib; Parameswaran, Parameswaran (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2021)
Monitoring is an activity that is carried out continuously. Healthy condition is a parameter that is needed in life, one of the important parameters is the measurement of oxygen saturation in the blood and heart rate. The purpose of this research is to develop a Smartwatch SpO2 device and BPM sensor that is connected to WIFI using the Android Platform instead of using an LCD for parameter reading. This module design method uses the MAX30100 sensor to display the SpO2 and BPM values ​​displayed on the OLED. Data processing is carried out using ATMEGA 328P programming and then displayed in the Android-based Mit-app application. The results show the average error for the SPO2 value is 0.868 % and the standard deviation is 0.170 %, while the BPM value has an average error of 0.56 % and a standard deviation of 0.30%. From the results of the comparison data analysis, the largest error was 1.03% and the smallest was 0.62% for Spo2 ml/hour with an accuracy of 0.05 (0.57%) with a precision value of 0.08 at the selection speed of 50 ml/hour. From the results above, it can be concluded that the data can be displayed on OLED using the Mit-app Android application with an error rate accuracy of 0.57%. From the results of this research design, it is hoped that it can facilitate the diagnosis of the condition of patients and health nurses